2016
DOI: 10.3389/fpls.2016.00853
|View full text |Cite
|
Sign up to set email alerts
|

Oligouridylate Binding Protein 1b Plays an Integral Role in Plant Heat Stress Tolerance

Abstract: Stress granules (SGs), which are formed in the plant cytoplasm under stress conditions, are transient dynamic sites (particles) for mRNA storage. SGs are actively involved in protecting mRNAs from degradation. Oligouridylate binding protein 1b (UBP1b) is a component of SGs. The formation of microscopically visible cytoplasmic foci, referred to as UBP1b SG, was induced by heat treatment in UBP1b-overexpressing Arabidopsis plants (UBP1b-ox). A detailed understanding of the function of UBP1b, however, is still no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 32 publications
1
44
0
1
Order By: Relevance
“…UBP1 acts as SGs' central component, and protects heat stress tolerance-related transcripts from exonucleolytic degradation via interactions with the 3 0 -UTR of mRNAs to play a fundamental role in thermotolerance. 13,21,22 In plants, another DNA-and RNA-biding family of proteins, the CCCH-type tandem zinc finger proteins (TZFs), colocalized with both SGs and P-bodies under various stressful conditions including heat and hypoxia. TZFs are highly conserved among eukaryotes and perform critical functions in mRNA metabolism in animals and yeast.…”
Section: Discussionmentioning
confidence: 99%
“…UBP1 acts as SGs' central component, and protects heat stress tolerance-related transcripts from exonucleolytic degradation via interactions with the 3 0 -UTR of mRNAs to play a fundamental role in thermotolerance. 13,21,22 In plants, another DNA-and RNA-biding family of proteins, the CCCH-type tandem zinc finger proteins (TZFs), colocalized with both SGs and P-bodies under various stressful conditions including heat and hypoxia. TZFs are highly conserved among eukaryotes and perform critical functions in mRNA metabolism in animals and yeast.…”
Section: Discussionmentioning
confidence: 99%
“…UBP1A and UBP1C reversibly aggregate Gloggnitzer et al (2014) into cytoplasmic poly(A) mRNA granules upon hypoxic and heat stress (Sorenson and Bailey-Serres, 2014). Similarly, UBP1B reversibly forms SGs under heat stress and plays a crucial role in ABA signaling and heat stress tolerance (Nguyen et al, 2016(Nguyen et al, , 2017). An analysis of RNA decay kinetics suggested that UBP1B complexes (UBP1B-SGs) protect stress-related mRNAs from degradation during heat stress (Nguyen et al, 2016).…”
Section: Mrna Sequestration In Sgs: a Transit Depot Between Translatimentioning
confidence: 99%
“…Similarly, UBP1B reversibly forms SGs under heat stress and plays a crucial role in ABA signaling and heat stress tolerance (Nguyen et al, 2016(Nguyen et al, , 2017). An analysis of RNA decay kinetics suggested that UBP1B complexes (UBP1B-SGs) protect stress-related mRNAs from degradation during heat stress (Nguyen et al, 2016). Likewise, UBP1C is required for plant survival of low-oxygen stress.…”
Section: Mrna Sequestration In Sgs: a Transit Depot Between Translatimentioning
confidence: 99%
“…Several potential targets of UBP1b, including mRNAs of a DNAJ binding protein and a zinc finger binding protein, were identified. 5 Our microarray analysis of UBP1b-ox plants subjected to non-stressed or heat stress conditions revealed higher expression of several ABA signaling-related genes, suggesting that the UBP1b functions in the ABA signaling pathway. Root elongation and seed germination assays demonstrated that UBP1b-ox plants exhibit an ABA-hypersensitive phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the molecular mechanisms responsible for environmental stress tolerance in plants is essential for developing strategies to improve plant productivity under unfavorable environmental conditions. Recent studies have revealed that post-transcriptional regulatory mechanisms, such as the addition of 5 0 cap structure, 1 splicing, 2 3 0 poly A addition, 3 and control of mRNA degradation 4 and storage, 5 are involved in stress response and adaptation.…”
Section: Introductionmentioning
confidence: 99%